Comparison of antioxidant properties of pomelo [Citrus Grandis (L) Osbeck] varieties - Toh, Jing Jing; Khoo, Hock Eng; Azlan, Azrina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This study aimed to compare the antioxidant content and antioxidant capacity of pulp and peel of two varieties of pomelo fruit (Tambun White and Tambun Pink). Antioxidants including total phenolic content, total flavonoid content and ascorbic acid content were determined using Folin-Ciocalteu reagent assay, aluminium chloride colorimetric assay and AOAC method, respectively. Antioxidant capacity of pomelo pulp and peel was measured using ferric reducing antioxidant potential and trolox equivalent antioxidant capacity assays. The peels of both pomelo fruits had higher antioxidant content and capacity than their pulps. Moreover, the white variety of pomelo had higher antioxidant content and capacity compared to the pink counterpart. Trolox equivalent antioxidant capacity of the samples was positively high correlated with total phenolic content (r = 0.978) and total flavonoid content (r =0.959), except for ascorbic acid. Therefore, pomelo peel from white variety possessed higher antioxidant properties and it is potentially rich sources of natural antioxidants.